ВЗАЄМОДІЯ СОЦІАЛЬНОГО ПЕДАГОГА ШКОЛИ З БАТЬКАМИ: ТЕНДЕРНИЙ ПІДХІД (Педагогіка вищої та середньої школи, 2009)
In this article are considered the problems of organization of senior's educational process based on the gender approach at comprehensive school, which is realized because of cooperation between school social teacher and parents.